Late hypertensive intraventricular pneumocephalus after a ventriculo-peritoneal shunting procedure: a case report - Casallo-Quiliano, Carlos (2012)
A 45-year-old male with neurocysticercosis complicated by hydrocephalus underwent a ventriculo-peritoneal shunt procedure because of secondary hydrocephalus. Four months afterwards he developed an intraventricular pneumocephalus and a porencephalic cyst in the right temporal lobe. Neuroradiology imaging studies did not show any bone defect in the base of the cranium, but a brain CT scan showed a porencephalic cyst located next to the right tympanic segment. An external ventricular shunt was placed and the former ventriculoperitoneal shunt was taken out, and neurological signs and symptoms improved. Afterwards, a right mastoidectomy and excision of the external shunt were performed. Control CT scans showed a progressive reduction in the intraventricular air contents. The patient was discharged with no symptoms affecting him. Two months later, pneumocephalus disappeared.